2015
DOI: 10.1007/s13197-015-1999-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the process parameters on osmotic dehydration of mapara (Hypophthalmus edentatus) fillet

Abstract: The effects of temperature, time, pressure and brine concentration were assessed during osmotic dehydration (OD) of H. edentatus fillet. The response surface methodology (RSM) showed that using vacuum during the OD process did not cause a statistically significant change (p>0.05) on the water loss (WL), solid gain (SG) and water activity (a w ). The other factors showed a statistically significant effect (p≤ 0.05) on at least one of these responses. Through RSM, the following condition could be defined for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…However, WL in this period (2 hours) was inversely proportional to the dry salting temperature. Lower WL was at 30 °C (4.97%), and the higher WL occurred at 10 °C (12.11%), an opposite behavior when compared with other studies that observed the temperature effect during osmotic dehydration [16,28,29,30]. After the dry salting process, WL was higher at 10 °C (33.99%) when compared to the other temperatures, while WL was lower at 15 °C (23.31%).…”
Section: Water Loss and Salt Gain During Dry Salting Processcontrasting
confidence: 61%
See 1 more Smart Citation
“…However, WL in this period (2 hours) was inversely proportional to the dry salting temperature. Lower WL was at 30 °C (4.97%), and the higher WL occurred at 10 °C (12.11%), an opposite behavior when compared with other studies that observed the temperature effect during osmotic dehydration [16,28,29,30]. After the dry salting process, WL was higher at 10 °C (33.99%) when compared to the other temperatures, while WL was lower at 15 °C (23.31%).…”
Section: Water Loss and Salt Gain During Dry Salting Processcontrasting
confidence: 61%
“…Schmidt, Carciofi and Laurindo (2008) [10] studied the osmotic dehydration process chicken breast and obtained a good fitting of the model to the experimental data for water loss and salt gain with Azuara et al (1992) [12]. The empirical model also showed an excellent proper fitting for pile salting of goat sheets [36] and the osmotic vacuum dehydration of mapará fillets [29]. a Parameters estimated by model from Azuara et al [12]: water loss in the equilibrium (WL ∞ in g/100g) and k constant; and b correlation coefficient (R 2 ) b statistical parameters by model from Azuara et al [12] to the experimental data.…”
Section: Water Loss and Salt Gain During Dry Salting Processmentioning
confidence: 91%
“…The NaCl concentration in the osmotic solution was the parameter that had the greatest effect on all responses and, consequently, on the OD process (Table 2), being positive for WL and SG and negative for a w . This behavior was observed by Maciel et al (2015) for OD of highwaterman catfish (Hypophthalmus edentatus) and by Medina-Vivanco et al (2002) for OD of tilapia (Oreochromis niloticus).…”
Section: Osmotic Dehydration Processmentioning
confidence: 77%
“…23) to the experimental data of SG in the CCD. Maciel et al (2012Maciel et al ( , 2015 established as optimal conditions 49°C and 28% NaCl for the OD of pirarucu at atmospheric pressure and 25°C, 25% NaCl for the OD of highwaterman catfish, respectively.…”
Section: Optimization Of the Osmotic Dehydration Processmentioning
confidence: 99%